2015
DOI: 10.1080/2162402x.2015.1075114
|View full text |Cite
|
Sign up to set email alerts
|

Repeated PD-1/PD-L1 monoclonal antibody administration induces fatal xenogeneic hypersensitivity reactions in a murine model of breast cancer

Abstract: Monoclonal antibodies (mAbs) targeting coinhibitory molecules such as PD-1, PD-L1 and CTLA-4 are increasingly used as targets of therapeutic intervention against cancer. While these targets have led to a critical paradigm shift in treatments for cancer, these approaches are also plagued with limitations owing to cancer immune evasion mechanisms and adverse toxicities associated with continuous treatment. It has been difficult to reproduce and develop interventions to these limitations preclinically due to poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 58 publications
8
55
0
Order By: Relevance
“…Others have also observed this fatal hypersensitivity after repeated injections of anti-PD1 (clone J43; hamster IgG) or anti-PD-L1 (clone 10F.9G2; rat IgG) in the syngeneic 4T1 tumor model and suggested that mortality was associated with neutrophil-mediated anaphylaxis involving accumulation of neutrophils in the lungs. 22 Surprisingly, we observed that this fatal hypersensitivity seen with anti-PD1 antibody was not seen when the PD1 blockade was in combination with SGT-53 (Figure 8A). Autopsies of our mice that had received five injections with anti-PD1 revealed massive infiltration of neutrophils and macrophages in the lung and liver (Figure 8B), and FACS analysis confirmed abnormalities reflecting neutrophil and macrophage infiltration in the lung (Figure 8C).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Others have also observed this fatal hypersensitivity after repeated injections of anti-PD1 (clone J43; hamster IgG) or anti-PD-L1 (clone 10F.9G2; rat IgG) in the syngeneic 4T1 tumor model and suggested that mortality was associated with neutrophil-mediated anaphylaxis involving accumulation of neutrophils in the lungs. 22 Surprisingly, we observed that this fatal hypersensitivity seen with anti-PD1 antibody was not seen when the PD1 blockade was in combination with SGT-53 (Figure 8A). Autopsies of our mice that had received five injections with anti-PD1 revealed massive infiltration of neutrophils and macrophages in the lung and liver (Figure 8B), and FACS analysis confirmed abnormalities reflecting neutrophil and macrophage infiltration in the lung (Figure 8C).…”
Section: Resultsmentioning
confidence: 88%
“…Hypersensitivity leading to death after repeated injections of xenogeneic anti-PD1 (clone J43; hamster IgG) or anti-PD-L1 (clone 10F.9G2; rat IgG) has also been observed by others using the 4T1 tumor model in BALB/c mice. 22 Increased accumulation of neutrophils in the lung and the neutrophil-induced anaphylaxis were identified as the cause of death. 22 We saw an abnormal lung infiltration of neutrophils only with anti-PD1 antibody monotherapy but not with either SGT-53 alone or with the combination of anti-PD1 and SGT-53 treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-2 has been reported to promote hypersensitivity reactions in patients receiving iodine containing radiographic contrast media at a higher incident than the general population [12,13]. Preclinical studies highlighted fatal hypersensitivity reactions in mice with 4T1 tumors exacerbated by blockage of PD-1/PD-L1 [14]. Adverse reactions to shellfish can be produced by immunological and nonimmunological reactions.…”
Section: Discussionmentioning
confidence: 99%
“…A similar hypersensitivity/ADA reaction has been recently described after a repetitive i.p. dosing with murine Ab treatments against checkpoint inhibitors (hamster anti-PD-1 and rat IgG2b anti-PD-L1) in a 4T1 tumor syngeneic model because of the xenogeneic nature of the Ab treatments (55). Strategies to mitigate risk factors from the clinical use of human protein therapeutics (i.e., humanization, CDR modification, formulation, biophysical characteristics, routes of delivery, etc.)…”
Section: Discussionmentioning
confidence: 99%